Strategi Pembelajaran Pendidikan Agama Islam Berbasis Multiple Intellegences - Yanti, Siti Ida; Irmayani; Siti Asiyah; Ma’ruf Ishak Ola (AL MURABBI, 2024)
The PAI Learning Strategy Based on Multiple Intelligences aims to develop students' abilities in understanding and practicing Islamic teachings according to their individual potential. This research describes the planning, implementation and evaluation of Islamic Religious Education (PAI) learning strategies based on multiple intelligences (MI) for class III students at SD Negeri 1 Bonipoi, using descriptive qualitative methods and case studies. Data was collected through observation, interviews and documentation, and analyzed through data condensation and display, as well as triangulation validation. Research results: 1) Planning: Includes MI identification through observing student activities and interviews, creating a syllabus and learning tools according to student intelligence, as well as preparing supporting media. 2) Implementation: Carried out with apperception, motivation, and MI-based activities, such as singing and reflection, as well as learning activities that are appropriate to student intelligence, such as verbal linguistics, logical-mathematical, visual-spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalist. 3) Evaluation: Does not use ratings, but rather authentic assessments that include cognitive, affective and psychomotor aspects.